Study on alkaloids from the roots of Murraya koenigii (IR) - Adilah Shahidan (2017)
The aims of this study were to determine the phytochemical constituents from the roots of Murraya koenigii and to test the antidiabetic activities. The isolation and purification of the chemical compounds involves extraction and separations by using various chromatographic methods and structural determination by specttroscopic techniques such as ultraviolet (UV), infrared (IR), mass spectroscopy (MS) and nuclear magnetic resonance (NMR) including 1D-NMR (1H, 13C and DEPT) and 2DNMR (COSY, HMQC and HMBC). The structure of the isolated compounds were compared with previous work done by other researcher. Isolation studies on the roots of Malayan M. koenigii collected from Jerantut, Pahang involving hexane, dichloromethane and methanol extract yielded eight compounds. Hexane crude extracts gave two compounds; girinimbine and murrayafoline A, while five compounds were successfully isolated from the dichloromethane crude extracts known as mahanimbine, murrayanine, 3-formylcarbazole, N-methoxy-3- hydroxymethyl-9H-carbazole and koenoline. Futher investigation on the methanol crude extracts afforded one new indole alkaloid named 2-hydroxy-3,5- dimethoxyindole. In a parallel investigation, the antidiabetic activity were also tested on all crude extracts and isolated compounds. It showed negative results on antidiabetic activity test. The implication of the data obtained from this study can be use as a reference for other researchers to conduct studies on M. koenigii. In conclusion, the study successfully isolated and purified eight compounds from roots of M. koenigii and tested for their antidiabetic activity.